International trade in health services - assessing the trade and the trade-offs - Jon Mortensen (Danish Institute for International Studies (DIIS), 2008)
International trade in health services has gained momentum – both in terms of increased trade and level of media, political and academic attention – over the past decade. International organisations, non-governmental organisations (NGOs) and academics have all contributed to a literature on the subject covering a wide range of perspectives and conclusions. As trade in services is broadly defined the literature covers aspects of all sides of the 'triangle' of economic globalisation: trade, investment and migration. Based on recent but scattered literature, the aim is to provide an overview of the commercial opportunities from trade in health services for developing countries and the trade-offs these are argued to be associated with. Based on recently published data, the paper estimates the global value of international trade in health services at USD 33 billion in 2005. It concludes that the literature often falls into one of two 'traps'. It either regards trade as a threat to public health that must be combated or it makes buoyant claims regarding the current and potential commercial opportunities from trade. Neither 'trap' is supported by empirical evidence. Achieving data of a quality and depth on trade in health services that is comparable to that available for trade in goods would be a helpful tool for policy makers, researcher and others trying to access the trade and 'trade offs' in cross-border health services delivery.
Keywords: 330; Gesundheitswesen; Gesundheitsversorgung; Internationaler Dienstleistungsverkehr; Entwicklungsländer